(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2020)
As a part of Proyecto Aves y Café, USCAFE, led by Provita, Organización no Gubernamental Ambientalista, is carrying out a diagnostic investigation as a baseline study, with a quantitative approach, on the socioenvironmental and sociocultural characteristics of the producers located in the Project area, some 200 hectares, established in La Piedra de Cachimbo, community adjacent to Colonia Tovar, in the mountainous area of Vargas State, Venezuela, through a survey applied to thirtyfive producers of the one hundred and twentysix that comprise it, as well as a workshop on the Problem Tree with twenty of them with organizational experience, and indepth interviews with four key informants. This baseline study provides the information that guides the provision of technical assistance to encourage the incorporation of sustainable agroforestry practices and increase the cultivation of organic products, especially shade coffee, and thus recover the habitat of migratory birds, contribute to the preservation of biodiversity and water sources and improve the living conditions of producers, which aims to encourage their organization and promote alternatives for marketing organic items that can obtain certification to access international markets.